Education studies and teacher education - Stephen Ward (Educational Futures)
State-directed curriculum and teaching methods, together with the competency-led compliance model which permeates teacher-training courses in and , have led to the demise of critical theory in teacher education. Non-teacher training undergraduate Education Studies, however, is a rapidly growing subject in universities today and offers the opportunity for the development of theory and a critical analysis of policy and practice. The nature of the subject is not yet well defined and a wide range of curricula live under the title of ‘Education Studies’. There is also variation in the extent to which courses claim to prepare students for initial teacher training. This paper explores the possibilities for Education Studies courses offered in and and examines their potential relationship to teacher training. A theoretical framework for Education Studies is proposed and it is suggested that a background in critical theory of education is an essential attribute for future teachers in enabling them to become thoughtful decision-makers and to resist the compliance culture of current teacher training. The work draws upon initial findings from the research carried out on undergraduate Education Studies courses in and . Particular curriculum examples are drawn from the Education Studies programme at Bath Spa University College.